혈류제한 운동과 최근 연구 동향: 기전, 응용 분야, 최신 연구 동향에 대한 종합적인 고찰 - 한성민; 소위영 (Exercise science (Seoul, Korea), 2025)
PURPOSE: Blood Flow Restriction (BFR) exercise is an innovative method that can induce strength and increase muscle hypertrophy, even with low-intensity resistance exercise. This study aimed to review the physiological mechanisms, safety, major research trends, and practical applicability of BFR exercises through a literature review. METHODS: This study analyzed articles on BFR exercises published between January 1, 2000, and December 31, 2024, by searching databases such as PubMed, Google Scholar, and Web of Science. Key terms such as “Blood Flow Restriction Training,” “Low-Intensity Resistance Exercise,” “Muscle Hypertrophy,” and “Safety of BFR” were used. Research on the mechanisms, effects, safety, and application of BFR exercises were summarized. RESULTS: Previous studies have shown that BFR exercise increases metabolic stress and mechanical tension, and promotes muscle protein synthesis. Notably, even at 20–50% of the one-repetition maximum, BFR can induce similar effects as high-intensity exercise. Additionally, BFR exercises can be effectively applied in various fields, such as enhancing athletic performance, preventing sarcopenia in older individuals, and improving function in patients with chronic diseases. However, some studies have indicated that BFR exercise may increase blood pressure and the risk of thrombosis, and caution should be exercised when it is applied to individuals with cardiovascular diseases. CONCLUSIONS: The BFR exercise is a promising method for increasing strength and muscle hypertrophy, even at low intensities, and can be widely applied in rehabilitation and sports training. However, to ensure safety, proper pressure settings and adherence to protocols are essential, and special care should be taken when applied to specific populations (e.g., individuals with hypertension or cardiovascular diseases). Future research should focus on the long-term effects of BFR exercises and the development of personalized protocols. KCI Citation Count: 0